2012
DOI: 10.1002/alr.21091
|View full text |Cite
|
Sign up to set email alerts
|

Safety of intradermal skin tests for inhalants and foods: a prospective study

Abstract: Intradermal skin tests for inhalants or foods, when performed with appropriate precautions, have a safety profile comparable to skin prick tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The maximum possible concentration of each allergen, or the largest tolerated dose, was achieved within 4 months in all cases treated by subcutaneous (SCIT) or 2 months for those on sublingual immunotherapy (SLIT) [ 24 , 25 ]. Patients were re-evaluated every 6 months or sooner.…”
Section: Methodsmentioning
confidence: 99%
“…The maximum possible concentration of each allergen, or the largest tolerated dose, was achieved within 4 months in all cases treated by subcutaneous (SCIT) or 2 months for those on sublingual immunotherapy (SLIT) [ 24 , 25 ]. Patients were re-evaluated every 6 months or sooner.…”
Section: Methodsmentioning
confidence: 99%
“…The dose of AIT was increased weekly, as tolerated. Either the maximum possible concentration of each allergen, or the largest tolerated dose was achieved within 4 months in all cases [28,29]. Patients were reevaluated every 5 to 6 months.…”
Section: Immunotherapymentioning
confidence: 99%
“…evaluated in 1456 patients was totally 3.6% (intradermal testing: 3.1%; skin prick testing 0.41%), and highest in females [ 25 ]. A study in 20,530 patients reported that 80 patients tested experienced systemic reactions, 13 of them more severe, and calculated a risk of 0.009 and 0.003% for experiencing a major reaction during skin prick testing [ 26 ].…”
Section: There Are Disadvantages In Skin Prick Testingmentioning
confidence: 99%